2021
DOI: 10.12659/ajcr.935029
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxicosis-Induced Cardiomyopathy Complicated by Refractory Cardiogenic Shock Rescued by Extracorporeal Membrane Oxygenation

Abstract: Patient: Male 53-year-old Final Diagnosis: Thyrotoxicosis-induced cardiomyopathy Symptoms: Dyspnea Medication:— Clinical Procedure: — Specialty: Cardiology • Critical Care Medicine Objective: Unusual clinical course Background: Thyrotoxicosis-induced cardiomyopathy is a rare but potentially life-threatening condition that occurs in less than 1% of thyrotoxic individuals. Severely impaired left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In cases of poorly controlled thyroid function, dilated cardiomyopathy typically starts with left ventricular hypertrophy and high cardiac output. However, as the disease progresses, biventricular dilatation and congestive HF with reduced ejection fraction become more common, as documented in the literature [5,[7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In cases of poorly controlled thyroid function, dilated cardiomyopathy typically starts with left ventricular hypertrophy and high cardiac output. However, as the disease progresses, biventricular dilatation and congestive HF with reduced ejection fraction become more common, as documented in the literature [5,[7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 98%
“…Among the numerous articles that have explored TCM in the literature [5,[7][8][9][10][11], this study, to the best of our knowledge, is one of the very few case reports of TCM presenting as heart failure with preserved ejection fraction (HFpEF) and only atrial involvement. Our findings provide a unique perspective that will advance the understanding of this rare condition and could lead to improved diagnosis and treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, this creates a hyperdynamic circulatory state [ 20 , 21 ]. While thyrotoxicosis has commonly been shown to contribute to the signs and symptoms of CHF [ 19 , 22 ], it has rarely been associated with the development of left ventricular systolic dysfunction [ 15 , 23 , 24 ]. Hyperthyroidism is a very rare (<1%) cause of dilated cardiomyopathy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dahl et al found that although 6% of thyrotoxic individuals developed symptoms of heart failure, less than 1% developed dilated cardiomyopathy with impaired left ventricular systolic function [ 16 ]. Additionally, case reports on the development of dilated cardiomyopathy with reduced ejection fraction (EF) secondary to thyrotoxicosis have been in middle-aged or elderly patients [ 14 , 15 ]. We present a novel case of a young patient who presented with thyrotoxicosis and subsequently developed dilated cardiomyopathy with reduced ejection fraction and global hypokinesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation